Fermentasi Singkong Karet (Monihot carthagenensis MÜII) menjadi Etanol dengan Pemanfaatan Albumin Dari Ikan Gabus (Channa striata) Sebagai Sumber Nitrogen Bagi Mikroba - Saputri Satriyana Widyaningrum; Rudi Kartika; Erwin Erwin (JURNAL KIMIA MULAWARMAN, 2022)
Has been cassava rubber fermentation (M. carthagenensisMÜll) as a raw material for making ethanol with the utilization of fishcork albumin (Channastriata) as nitrogen Saccharomyces cerrevisiae with enzymatic hydrolysis result through 2 stages ieliquification using α-amylase and saccharification stage using gluco -amilase. The best reducing sugar content was obtained at 0.1307%. Based on this research, maximum ethanol content was obtained with 0.5% concentration of nutrient at fermentation time for 232 hours, obtained by result of 12,688% at 5.6 mL distillate volume using gas chromatography method.